2019
DOI: 10.1016/j.jtcme.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium taurate attenuates progression of hypertension and cardiotoxicity against cadmium chloride-induced hypertensive albino rats

Abstract: The present study was designed to evaluate the antihypertensive activity and cardioprotective effects of magnesium taurate against cadmium chloride (CdCl2)-intoxicated albino rats. Sprague Dawley male albino rats (120–150 g) were divided into five groups having six animals in each group. Hypertension and cardiotoxicity were induced in animals by administration of CdCl2 (0.5 mg/kg/day, i.p.) for four weeks. Magnesium taurate (2 and 4 mg/kg/day) was administered orally after induction of hypertension (after two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
3
0
0
1
Order By: Relevance
“…Another component of DASH diet that is considered as a decreasing factor of HTN, is magnesium, which in our study was shown as a preventive factor, and ths is fully consistent with the findings of other studies [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Another component of DASH diet that is considered as a decreasing factor of HTN, is magnesium, which in our study was shown as a preventive factor, and ths is fully consistent with the findings of other studies [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to those reported previously [68][69][70]. It has been demonstrated by some researchers that exposure to Cd can either inhibit these enzymes transiently or may interfere with their expression during transcriptional event [71].…”
Section: Discussionsupporting
confidence: 92%
“…Another component of DASH diet which is considered as a decreasing factor of HTN is magnesium which in our study showed to be preventive factor which is fully consistent with the ndings of other studies [25][26].…”
Section: Discussionsupporting
confidence: 93%